INTERAKSI AKTOR DALAM PENGENDALIAN LAHAN PERTANIAN DI KOTA PEKANBARU TAHUN 2012-2013 - Setiadi, Aidil Darma; Ridwan, Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Control of land in the city of Pekanbaru is a significant problem and actually is of particular concern. With the issuance of Law No. 41 of 2009 on the Protection of Agricultural Land Berkelanjutan.Penelitian aims to study the interaction of these actors in the control of agricultural land conversion to residential land in the city of Pekanbaru. The method used in this study is metodede skriptif. Methods descriptive study carried out by analyzing the data and facts. Data was collected using interview techniques, observation and documentation.To get the data and information in-depth interviews conducted with the actors involved. Informants were selected based sampling nonprobabilitiy by purposive sampling that only people who are experts and understand phenomena. In purposive sampling, researchers considerations play a role, even decisive in making a set of objects to be studied. It is clear that the value obtained based on a sample of research depends on researchers who give considerationThe results showed the interaction of the actors in the control of agricultural land in the city of Pekanbaru occurred between the Department of Spatial Planning and the Mayor's Office for Spatial Pertanian.Dinas provide the area or place for agriculture, but people who want to cultivate agricultural land must take care of permission to the mayor through Pertanian.Setelah Department permission, new people can cultivate land tersebut.Alih function of agricultural land in the city of Pekanbaru done by the owner of the land or the land itself. Because in Pekanbaru city average of agricultural land owned by an individual or individuals. In addition, the socialization of land conversion is still very lacking in Pekanbaru. Because when the author survey, the author has not met the appeal of the ban fungsian diversion of agricultural land.Keywords: Interaction, Land Management, Landlord